IoT based Smart Motor Cycle Helmet - Shahare, Bhavesh; Chawde, Shivani; Gudafwar, Rakesh; Pal, Harshada; Bobade, Purvi; Bawankar, Shyam (Journal of Electronics and Informatics, 2021)
The main purpose of this paper is to urge the two wheeler motor cycle riders to wear a helmet. In India, most of the death cases occur due to the two wheeler accidents. In most of the cases, rider suffers head injuries, which leads to death. In order to reduce the number of accidents, this research work proposes a smart helmet, which will be very useful for the two-wheeler riders. In general, two-wheeler accidents occur due to the high consumption of alcohol by the rider. The proposed smart helmet ensures the safety of the rider, while driving on the road. The proposed model comprises of an alcohol detection, accident identification, location tracking, hands-free device, solar powered module and fall detection. The proposed smart helmet will be connected to the ignition. Henceforth, if the rider does not wear a helmet, the ignition will not be triggered to start the two-wheeler. For handling an emergency situation, GSM module is used to send an alert message to the registered mobile number.